Keterampilan Menulis Cerita Pendek Berdasarkan Gambar Seri Berbasis Digital Pada Tema 9 Subtema 2 Pembelajaran 9 Semester 1 Kelas VI SD Hang Tuah 10 Juanda - Sinta Suroiya (CV. Ulil Albab Corp, 2022)
The purpose of this study (1) To describe short story writing skills based on digital-based series images of students of grade VI Hang Tuah 10 Juanda Elementary School. This study included a type of descriptive quantitative research with a sample of 32 students with calculations using suspension. Data collection using test methods and questionnaires. The data analysis technique used is a score category. The results of this study are: (1) The results of the learning resulted in the skill of writing short stories based on series pictures. Then the average calculation result is 81. The highest score is 100 and the lowest value is 63 with a total of 32 students. It proves that the class studied using digital-based serial image media obtained a complete score. This can be seen from the results of the categorization can be said to be successful if X ≥ 79.